Elucidation of inactivated microbial with Sargassum sp. as immunostimulants against Vibrio parahaemolyticus inducing acute hepatopancreatic necrosis disease in Penaeus vannamei (Boone, 1931) - Md. Ali, Amatul Samahah (2023)
Acute hepatopancreatic necrosis disease (AHPND) is an emerging disease in shrimp aquaculture industry caused by Vibrio parahaemolyticus. It imposes a serious threat to shrimp production through mass mortality of post-larval shrimp resulting USD 1 billion loss to the shrimp industry worldwide including Malaysia. Therefore, this study aimed to characterize V. parahaemolyticus strains causing AHPND in shrimp from a local shrimp farm in Malaysia, to develop an inactivated microbial immunostimulant from V. parahaemolyticus for protection against AHPND in shrimp, to conduct immunization trials of the inactivated microbial in combination with Sargassum sp. as immunostimulants in shrimp infected with AHPND, and to study the effect of immunization in shrimp immune system at the transcriptional level. In this study, isolates associated with AHPND outbreak had been isolated previously from a shrimp farm in Terengganu, Malaysia, and were further characterized. Based on the phenotypic characterization and phylogenetic analysis, strain C2A and C4B were identified as V. parahaemolyticus, meanwhile, strain C1B, C2B, C4A, and C5 were V. harveyi. This study suggested that, in Malaysia, both V. parahaemolyticus and V. harveyi could be the pathogen that caused AHPND outbreak in a local shrimp farm. The most virulent AHPND positive isolate in this experiment is V. parahaemolyticus C4B. The draft genome sequence of C4B were also compared with V. parahaemolyticus P24 which is a non-causing AHPND strain. The genome assembly metrics for revealed features transposons and insertion sequences, and bacteriophages are more abundant in the V. parahaemolyticus VPAHPND C4B genome compared to V. parahaemolyticus VPNONAHPND, P24, reflecting the organism’s genome plasticity and pathogenic features. Despite these variations, all genomes exhibited greater than 98.0% average nucleotide identity (ANI), indicating they belong to the same species. Notably, V. parahaemolyticus AHPND strains NCKU_TV_5HP and NCKU_CV_CHN showed ANI indices of 98.46% and 98.43%, respectively, when compared to strain C4B. Next is to develop an inactivated bacterial with Sargassum sp. as immunostimulants as potential protection against the AHPND in shrimp. The treatment group for this study was as follows, group 1: commercial feed, group 2: immunostimulant 1x103 CFU kg/feed, group 3: immunostimulant 1x105 CFU kg/feed, group 4: immunostimulant 1x107 CFU kg/feed, group 5: immunostimulant 1x103 CFU kg/feed + 2% Sargassum sp., group 6: immunostimulant 1x105 CFU kg/feed + 2% Sargassum sp., group 7: immunostimulant 1x107 CFU kg/feed + 2% Sargassum sp., and group 8: 2% Sargassum sp. After four weeks of the treatment period, immunostimulants with Sargassum sp. treatment groups (groups 5, 6, and 7) showed the highest percentage (>60%) of shrimp survival compared to treatment groups without Sargassum sp. Meanwhile, group 6 showed the highest shrimp survival after four weeks of immunization. After the challenge study, group 6 also showed the highest survival percentage, 64% compare to other treatment groups indicating that the immunostimulant of 1×105 CFU with Sargassum sp. was the best treatment in this study to increase disease against AHPND and to prevent mortalities in shrimp. The effect of the immunization using the immunostimulants had been further elucidated at the transcriptional level to find out its immune response on immunized shrimp’s gene expression compared to control group. Based on the differentially expressed genes (DEGs) detected in the KEGG pathway database, several notable changes in the immune-related genes such as antimicrobial peptides (anti-lipopolysaccharide factor, penaeidin, crustin), prophenoloxidase (proPO) gene cascade and upregulation of antioxidant gene expressions were identified following the immunization. This study's findings provide recent data on AHPND-associated isolates such as V. parahaemoluticus and V. harveyi, insights into the genome and its virulence, and information on the use of inactivated microbial with Sargassum sp. as immunostimulants as a means of disease protection coherent for sustainable prawn global production.